Diet of the Golden Eagle during the breeding season in northwestern Chihuahua, Mexico - Morales-Yañez, Isaac; Gatica Colima, Ana Bertha; Rodríguez-Estrella, Ricardo (2021)
The diet of the Golden Eagle (Aquila chrysaetos) was studied in 4 territories in northwestern Chihuahua, México, during the breeding season. Prey remains and pellets were collected from 4 nests during 2014, 2015, and 2016. We identified 12 vertebrate species. Black-tailed jackrabbits (Lepus californicus) were the most important prey remains in terms of frequency (72%) and ingested biomass (86%). We estimated mean prey size to be 1291 g (SE = 3364), indicating that Golden Eagles prey on medium-sized animals (e.g., lagomorphs). The main threats to Golden Eagles are connected to habitat loss and habitat fragmentation, but other factors also affect eagles. We hope our information will help to establish better species management programs.